PENGARUH KECERDASAN SPIRITUAL DAN KECERDASAN INTELEKTUAL TERHADAP PEMAHAMAN AKUNTANSI DI MASA PEMBELAJARAN DARING COVID-19 (Studi Empiris Pada Mahasiswa Akuntansi 2018 di Universitas Islam Malang dan Politeknik Negeri Malang) - Eltari Kusuma Dewi; Afifudin Afifudin; Hariri Hariri (Universitas Islam Malang, 2022)
The purpose of this study was to determine the effect of courageous learning in the Covid-19 era, spiritual intelligence, and intellectual intelligence carried out at the Islamic University of Malang and the State Polytechnic of Malang. In writing this study, samples were taken from accounting students in 2018 at the Islamic University of Malang and the State Polytechnic of Malang. The method of determining the sample uses purposive sampling using Slovin's formulas. The method of data analysis used was multiple linear regression analysis, with the method of collecting data using questionnaires or questionnaires distributed in a closed manner to respondents. Based on the research, the results show that (1) Spiritual intelligence and intellectual intelligence together influence accounting understanding during the Covid-19 learning period, (2) Spiritual intelligence negatively affects accounting understanding during the Covid-19 learning period, (3) Intellectual intelligence have a positive effect on understanding accounting during the Covid-19 brave learning period.Keywords: Spiritual Intelligence, Intellectual Intelligence, Accounting Understanding